The Style of Creative Behavior as a model of explaining response to music - Strzałecki, Andrzej; Skorupska, Monika (Studia Psychologica: Theoria et praxis, 2003)
The senior author’s model of The Style of Creative Behavior (CBQ), the five-factor model of the NEO personality inventory by Costa and McCrae (NEO-FFI), and Strelau’s Temperament Inventory from the model of the Formal Characteristic of Behavior (FCB-TI) were used to explain determinants of forming cognitive representations of music. A group of young people from a school of music and from a high-school (N=74) described in a specially constructed “Musical differential” (MD) their response to four pieces of music. Two excerpts (fast and slow) from Stravinsky’s work and two pieces (fast and slow) from Metallica’s album Reload were used as stimuli. The scores given by subjects to the pieces of music in three factors of MD: “Artistic evaluation”, “Formal structure”, and “Emotional reaction” were taken as dependent variables, while scores in questionnaires from models of CBQ, NEO-FFI, and FCB-TI were used as independent variables. The regression analysis was applied to explain variances of the four musical excerpts vered by dimensions of “Musical differential”. The results showed that personality factors responsible for creative behavior play an important role in cognitive representations of music.